Hypermobility in adolescent athletes: Pain, functional ability, quality of life, and musculoskeletal injuries - Schmidt, H.; Lykke Pedersen, T.; Junge, T.; Engelbert, R.; Juul-Kristensen, B. (Journal of Orthopaedic & Sports Physical Therapy, 2017)
Generalised joint hypermobility (GJH) may increase pain and likelihood of injuries and also decrease function and health-related quality of life (HRQoL) in elite level adolescent athletes. Objectives: To assess the prevalence of GJH in elite level adolescent athletes, and to study the association of GJH with pain, function, HRQoL, and musculoskeletal injuries. Methods: A total of 132 elite level adolescent athletes (36 males; 96 females), mean (SD) age 14.0 (0.9) years, participated (n=22 ballet dancers, n=57 teamgym gymnasts, n=53 team handball players). GJH was classified using the Beighton scores (BS) (GJH4: BS = 4/9, GJH5: BS = 5/9, GJH6: BS = 6/9). Function of lower extremity, musculoskeletal injuries, and HRQoL were assessed with self-reported questionnaires, and part of physical performance was assessed by 4 postural sway tests and 2 one-legged hop for distance tests. Results: Overall prevalence for GJH4, GJH5 and GJH6 was 27.3%, 15.9%, and 6.8%, respectively, with a higher prevalence in ballet dancers and team gymnasts than in team handball players (GJH4: 68.2%, 24.6%, and 13.2 %). There was no significant difference in lower extremity function, injury prevalence and related factors (exacerbation, recurrence, and absence from training) HRQoL, or lengths of hop tests for those with and without GJH. However, the GJH group had significantly larger centre of pressure path length across sway tests. Conclusion: For ballet dancers and teamgym gymnasts the prevalence of GJH4 was higher than for team handball players. For ballet dancers, the prevalence of GJH5 and GJH6 was higher than for team handball players and the general adolescent population. The GJH group demonstrated larger sway in the balance tests, which, in the current cross-sectional study did not have an association with injuries or HRQoL. However, the risk of having (ankle) injuries due to larger sway for the GJH group must be studied in future longitudinal studies